Improving child survival under National Health Mission in India: Where do we stand? - Khurmi, Manpreet; Gupta, Medhavi; Patle, Ajay; Kaur, Prabhjot; Mathur, Nimisha; Chaudhari, Gaurav; Prabhakar, P K; Mohammed, Suresh K; Khera, Ajay (Indian Journal of Child Health, 2015)
India contributes to around one-fifth of the global under-five mortality and also maternal mortality besides one-third of the neonatal mortality. Since any reduction in child mortality in India is crucial for the global decline, therefore, the Indian Government decided to undertake massive correction of the health system. This led to the launch of National Rural Health Mission in the year 2005. Since then, significant progress has been made and child mortality rates have shown a sharp decline. On comparing the progress made by the world toward Millennium Development Goals, India fares better by showing a decline of 46.5% in comparison to 41% for the entire world during the same period. In order to assess the state-wise reduction, data from sample registration system of the Registrar General of India which is available for most of the States/Union Territories (UTs) have been analyzed. States such as Maharashtra, Tamil Nadu, and Kerala have shown an impressive decline but some states such as Himachal Pradesh, Punjab, Mizoram, and Delhi still have a long way to go to reach the state specific goals and targets. Any further decline would only be possible by addressing inter-district variations that are still lagging behind and focused efforts need to be made, in order to reach these desired goals. This analysis would be valuable in planning future program implementation plans.